A new species of Acidocroton Section Ophellantha (Euphorbiaceae) in Tabasco, Mexico - Hanan-Alipi, Ana M.; Steinmann, Victor W. (Instituto de Ecología, A.C., 2013)
The new species Acidocroton madrigalensis is described and illustrated from the state of Tabasco, Mexico. It is known only from the Sierra El Madrigal and the Cerro La Campana, where it is a frequent component of the under story of tropical rain forest, occurring on limestone outcrops. It belongs to section Ophellantha and is characterized by its diminutive, non-spinous stipules, large leaves that are shortly petiolate, and staminate flowers with 20 to 35 stamens. A table is presented that provides the principal differences among A. madrigalensis and the other two species of the genus present in Mexico, A. spinosus y A. steyermarkii.